Tantangan dan Faktor yang Mempengaruhi Penundaan Implementasi Pajak Karbon di Indonesia - Sofiyati, Rizqy Alifa; Hermawan, Sapto (Fakultas Syariah Institut Agama Islam Negeri Palu, 2023)
This research analyzes the challenges and factors influencing the delayed implementation of carbon tax in Indonesia using a qualitative descriptive approach through literature review and document analysis. The research findings indicate that the challenges and factors affecting the delay in carbon tax implementation can be seen from various aspects. This study has shown that the challenges in the carbon tax implementation process include the balance between environmental goals and economic well-being, public awareness and acceptance, infrastructure readiness and emission monitoring, as well as weak law enforcement in carbon tax policy determination. Various factors influencing the delay in carbon tax implementation include dependence on fossil energy sources, resistance from affected industries, the absence of a carbon tax roadmap, and unclear carbon exposure thresholds. With this research, it is hoped to provide an in-depth understanding of Indonesia's unique challenges in addressing climate change and offer insights needed to design effective policies for reducing carbon emissions and achieving environmental protection goals while considering existing socio-economic impacts.